In figure given above, ABC is a right triangle right angled at C. If D is midpoint of BC, prove that AB² = 4AD² - 3AC²
Attachments:
![](https://hi-static.z-dn.net/files/d66/a0c6b5865c6b06324fda0720fc15099a.jpg)
Answers
Answered by
2
Given :
∠C = 90° and D is the mid-point of BC.
In ∆ ACD,
AD² = AC² + CD²
[By using Pythagoras theorem]
CD² = AD² - AC² ……….(1)
In ∆ACB,
AB² = AC² + BC²
[By using Pythagoras theorem]
AB² = AC² + (2CD)²
[D is the mid-point of BC]
AB² = AC² + 4CD²
AB² = AC² +4(AD² - AC²)
[from eq 1]
AB² = AC² + 4AD² - 4AC²
AB² = 4AD² - 4AC² + AC²
AB² = 4AD² - 3AC²
PLEASE MARK ME AS THE BRAINLIEST
Similar questions
Computer Science,
2 months ago
History,
2 months ago
Biology,
2 months ago
Math,
4 months ago
Physics,
4 months ago
Social Sciences,
11 months ago
Hindi,
11 months ago